Influence Of Emotional Intelligence And Spiritual Intelligence On Employee Performance At The Palopo City Agriculture Department - Mutiara Magnalia; Indra Kusdarianto; Haedar Haedar (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims to analyze the effect of emotional intelligence and spiritual intelligence on employee performance at the Agricultural Office of Palopo City. Methodology: This research uses a quantitative approach with a survey method. The population consists of all employees of the Palopo City Agricultural Office. Data were collected through questionnaires and analyzed using multiple linear regression analysis with SPSS. Results: The results show that emotional intelligence has a positive and significant effect on employee performance (B = 0.542, p < 0.001). Spiritual intelligence also has a positive and significant effect on employee performance (B = 0.405, p < 0.001). Simultaneously, emotional and spiritual intelligence significantly influence employee performance. Findings: These findings indicate that higher levels of emotional and spiritual intelligence contribute to better employee performance. Emotional intelligence has a more dominant influence compared to spiritual intelligence. Novelty & Originality: This study provides novel empirical evidence on the combined role of emotional and spiritual intelligence in an under-researched context, namely a local government agricultural office in eastern Indonesia. Conclusions: Emotional intelligence and spiritual intelligence significantly improve employee performance. Therefore, developing both types of intelligence should become a strategic priority in human resource management within local government institutions. Type of Paper: This paper is an empirical research paper.